O reforço das competências de gestão nas instituições públicas: governança e gestão no poder legislativo municipal: estudo de caso na Câmara Municipal de Niterói - Almeida, Evandro Julião de (2006)
This thesis analyzes the governance in public institutions management, taking the Niteroi's Cityzenship Council as the reasearch object. In order to accomplish this goal, this thesis has been split into two parts. The first one introduces the discussion about management, manager's action and administration, differentiating the private approach from the public one. The characteristics of the public service and its models were defined, as they were incorporated in the last decades in parallel with the institutionalism and governance theories. In the second part a description is presented on the Brazilian's politician space construction, with emphasis in the cities and in the functioning of the public institutions according to the reality of the Brazilian's partisan system. The concept of accountability and the relation between repuplican powers were also discussed, followed by a case study. The analyses show the reality of the governance at the chamber of the councilmen of Niteroi in accordance with the methodology chosen to accomplishment the research. The conclusion points out the findings that were obtained during the research.